Annulated Dialkoxybenzenes as Catholyte Materials for Non‐aqueous Redox Flow Batteries: Achieving High Chemical Stability through Bicyclic Substitution. Issue 21 (21st July 2017) - Zhang, Jingjing; Yang, Zheng; Shkrob, Ilya A.; Assary, Rajeev S.; Tung, Siu on; Silcox, Benjamin; Duan, Wentao; Zhang, Junjie; Su, Chi Cheung; Hu, Bin; Pan, Baofei; Liao, Chen; et al.
Abstract: 1, 4‐Dimethoxybenzene derivatives are materials of choice for use as catholytes in non‐aqueous redox flow batteries, as they exhibit high open‐circuit potentials and excellent electrochemical reversibility. However, chemical stability of these materials in their oxidized form needs to be improved. Disubstitution in the arene ring is used to suppress parasitic reactions of their radical cations, but this does not fully prevent ring‐addition reactions. By incorporating bicyclic substitutions and ether chains into the dialkoxybenzenes, a novel catholyte molecule, 9, 10‐bis(2‐methoxyethoxy)‐1, 2, 3, 4, 5, 6, 7, 8‐octahydro‐1, 4:5, 8‐dimethanenoanthracene (BODMA), is obtained and exhibits greater solubility and superior chemical stability in the charged state. A hybrid flow cell containing BODMA is operated for 150 charge–discharge cycles with a minimal loss of capacity. Abstract : A novel bicyclical substituted dialkoxy‐benzene molecule, 9, 10‐bis(2‐methoxy‐ethoxy)‐1, 2, 3, 4, 5, 6, 7, 8‐octahydro‐1, 4:5, 8‐dimethanenoanthracene (BODMA), is developed for use as catholyte materials in non‐aqueous redox flow batteries with greater solubility (in their neutral state) and improved chemical stability (in their charged state). A hybrid flow cell using BODMA demonstrates stable efficiencies and capacity over 150 cycles. The molecular design approach of BODMA can be inspirational for future development of redox active molecules.